Surface modified fiber, reinforcing fiber, and molded article using the reinforcing fiber

By forming a surface modification layer with a specific Zeta potential on the fiber surface and using an adhesive layer with a conjugated diene rubber, the problems of carcinogenicity and environmental pollution in the prior art are solved, and the fiber-rubber bonding effect with high strength and high elastic modulus is achieved.

CN114787443BActive Publication Date: 2025-04-11KURARAY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080082717.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-27
Filing Date
2020-11-10
Publication Date
2025-04-11
Estimated Expiration
2040-11-10

AI Technical Summary

Technical Problem

Adhesives using resorcinol and formaldehyde in the prior art have problems of carcinogenicity and environmental pollution, and their adhesiveness is also poor, making it difficult to meet the needs of high strength and high elastic modulus.

Method used

By forming a surface modification layer on the fiber surface, the Zeta potential of the fiber is adjusted to a range of -20.0 to 30.0 mV, and an adhesive layer containing a conjugated diene rubber is used to improve the adhesion between the fiber and the rubber.

Benefits of technology

It realizes that the adhesion between fiber and rubber is improved without using resorcinol and formaldehyde, and the reinforcement performance of fiber is enhanced. The process is simple and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003665661380000251
    Figure GDA0003665661380000251
  • Figure GDA0003665661380000281
    Figure GDA0003665661380000281
  • Figure GDA0003665661380000291
    Figure GDA0003665661380000291
Patent Text Reader

Abstract

The present invention provides a surface-modified fiber, a reinforcing fiber, and a molded body using the reinforcing fiber that can improve adhesion to rubber without using resorcinol and formaldehyde. The surface-modified fiber comprises a fiber and a surface-modified layer covering at least a portion of the surface of the fiber, and the surface of the surface-modified layer has a solid surface Zeta potential of -20.0 to 30.0 mV.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a surface-modified fiber having excellent adhesiveness to rubber, a reinforcing fiber, and a molded product using the reinforcing fiber. Background Art

[0002] Synthetic organic fibers such as polyethylene terephthalate (PET), nylon 66, vinylon, and rayon are cheap, have high strength, excellent heat resistance, durability, and are lightweight, and are therefore used as reinforcing fibers for automobile tires and brake hoses. In these products, in order to bring out the excellent physical properties of rubber (e.g., high strength and high elastic modulus), it is necessary to firmly bond the fiber to the rubber.

[0003] As a method for firmly bonding fibers and rubber, a method using an adhesive called RFL having resorcinol-formaldehyde resin and rubber latex as main components is widely known (Patent Documents 1 and 2).

[0004] However, formaldehyde contained in RFL is suspected to be carcinogenic, and resorcinol is suspected to be an environmental hormone, so it is desired to develop alternative materials that do not use these raw materials.

[0005] As an alternative material to RFL, for example, Patent Document 3 proposes a technique of using an adhesive containing an adhesive compound having an unsaturated carbon bond and an epoxy group that react with a vulcanizing agent used for rubber vulcanization. In addition, Patent Document 4 proposes a technique of providing an active functional group layer by providing a blocked isocyanate compound and an epoxy compound in the first stage and using an adhesive component containing latex as a main component in the second stage.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 54-4976

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 58-2370

[0010] Patent Document 3: Japanese Patent Application Publication No. 2011-111563

[0011] Patent Document 4: European Patent No. 3258006 Summary of the invention

[0012] Problems to be solved by the invention

[0013] Compared with the existing method using RFL, the method using adhesive described in Patent Document 3 has the problem of significantly poorer adhesion and lack of practicality. In addition, the treatment described in Patent Document 4 requires a process of setting up an intermediate layer called a rubber coating, and requires heat treatment at high temperature in two stages. Therefore, the treatment requires a large amount of energy and there is a risk of thermal degradation of the fiber, and sometimes the reinforcement performance is reduced. It should be noted that Patent Document 4 only describes the technology of using an adhesive component with latex as the main component, and there is no record of using an adhesive component with conjugated diene rubber as the main component.

[0014] The present invention has been made in view of the above-mentioned conventional problems, and an object of the present invention is to provide a surface-modified fiber, a reinforcing fiber, and a molded product using the reinforcing fiber, which can improve the adhesion to rubber without using resorcinol and formaldehyde.

[0015] Solutions to the problem

[0016] The inventors of the present invention conducted intensive research to solve the above-mentioned problems and found that by allowing specific compounds to adhere to the fibers, the Zeta potential of the fiber surface is adjusted to a specific range, thereby increasing the affinity between the fibers and the adhesive component. As a result, even without using resorcinol and formaldehyde, the adhesion between the fibers and rubber is improved, thereby completing the present invention.

[0017] That is, the present invention relates to the following [1] to

[14] .

[0018] [1] A surface-modified fiber comprising a fiber and a surface-modified layer covering at least a portion of a surface of the fiber, wherein the surface of the surface-modified layer has a solid surface zeta potential of -20.0 to 30.0 mV.

[0019] [2] The surface-modified fiber according to [1] above, wherein

[0020] The fiber is one or more fibers selected from the group consisting of polyester fibers, polyamide fibers, polyvinyl alcohol fibers, and regenerated cellulose fibers.

[0021] [3] The surface-modified fiber according to [1] or [2] above, wherein:

[0022] The surface modification layer contains a compound having a nitrogen-containing functional group.

[0023] [4] The surface-modified fiber according to any one of [1] to [3] above, wherein

[0024] The surface modification layer comprises a Oxazoline, A compound having one or more functional groups selected from the group consisting of an oxazolidinone group, a carbodiimide group, a ureido group, an amino group, and an aziridine group.

[0025] [5] The surface-modified fiber according to any one of [1] to [4] above, wherein

[0026] The amount of the surface modification layer is 0.01 to 5.0 parts by mass based on 100 parts by mass of the fiber used as a raw material.

[0027] [6] A reinforcing fiber having:

[0028] The surface-modified fiber according to any one of [1] to [5] above, and

[0029] An adhesive layer containing a conjugated diene rubber and covering at least a portion of the surface of the surface-modified fiber.

[0030] [7] The reinforcing fiber according to [6] above, wherein

[0031] The number average molecular weight (Mn) of the conjugated diene rubber is more than 2,000 and 120,000 or less.

[0032] [8] The reinforcing fiber according to [6] or [7] above, wherein

[0033] The conjugated diene rubber has at least one monomer unit derived from butadiene, isoprene, and farnesene in the molecule.

[0034] [9] The reinforcing fiber according to any one of [6] to [8] above, wherein

[0035] The above-mentioned conjugated diene rubber is a modified conjugated diene rubber having a hydrogen-bonding functional group in a part of the conjugated diene rubber, and the hydrogen-bonding functional group is one or more selected from a hydroxyl group, an epoxy group, an aldehyde group, an acetalized form of an aldehyde group, a carboxyl group, a salt of a carboxyl group, an esterified form of a carboxyl group, an anhydride of a carboxyl group, a silanol group, an esterified form of a silanol group, an amino group, an imidazole group, and a mercapto group.

[0036]

[10] The reinforcing fiber according to any one of [6] to [9] above, wherein

[0037] The adhesive layer further contains oil having a vapor pressure of 10 Pa or less at 20°C.

[0038]

[11] A molded product using the reinforcing fiber according to any one of [6] to

[10] above.

[0039]

[12] The molded article according to

[11] above, further comprising a rubber layer.

[0040]

[13] The molded article according to

[11] or

[12] above, wherein

[0041] The molded body is a tire, a belt or a tube.

[0042]

[14] A molded article comprising fibers, a surface modification layer, an adhesive layer, and a rubber layer in this order,

[0043] The adhesive strength between the adhesive layer and the rubber layer is 70 N or more per a width of 25.4 mm.

[0044] Effects of the Invention

[0045] The present invention can provide a surface-modified fiber capable of improving adhesion to rubber without using resorcinol and formaldehyde, a reinforcing fiber, and a molded product using the reinforcing fiber. DETAILED DESCRIPTION

[0046] [Surface modified fiber]

[0047] The surface-modified fiber of the present invention is characterized by comprising a fiber and a surface-modified layer covering at least a portion of the surface of the fiber, wherein the surface of the surface-modified layer has a solid surface zeta potential of -20.0 to 30.0 mV.

[0048] According to the present invention, since the zeta potential of the solid surface is adjusted to the above range, the modified conjugated diene rubber contained in the adhesive component and the fiber show strong affinity. Therefore, the fiber, the adhesive component and the rubber are firmly bonded to each other, and as a result, the adhesion between the fiber and the rubber is improved.

[0049] It should be noted that, in the present invention, "a surface modification layer covering at least a portion of the surface of the fiber" may refer to a mode in which the surface modification layer exists on at least a portion of the surface of the fiber, for example in the form of a film or layer, or may refer to a mode in which a component equivalent to the surface modification layer is included in the raw material of the fiber and the component of the surface modification layer exists on a portion of the surface of the fiber itself.

[0050] From the viewpoint of improving the affinity between the fiber and the adhesive component, thereby improving the adhesion between the fiber and the rubber, the solid surface Zeta potential of the surface of the surface modified layer is preferably -20.0 to 20.0 mV, more preferably -15.0 to 15.0 mV, further preferably -10.0 to 12.0 mV, further preferably -5.0 to 10.0 mV, further preferably -5.0 to 9.0 mV, further more preferably -5.0 to 6.0 mV, and further more preferably -5.0 to 0 mV.

[0051] <Surface modification layer>

[0052] The surface modification layer in the present invention is not particularly limited as long as it is composed of a compound capable of adjusting the zeta potential of the solid surface to the above range. For example, it is preferably a layer containing a compound having a nitrogen-containing functional group, specifically, it is preferably a layer containing a compound selected from Oxazoline, A layer of a compound having one or more functional groups selected from the group consisting of oxazolidinone group, carbodiimide group, urea group, amino group, and aziridine group.

[0053] Examples of the compound having the functional group include: Oxazolidinone compounds, The oxazoline group is introduced into the main chain of the polymer of acrylic acid or styrene / acrylic acid copolymer to obtain Azoline group-containing compound, a carbodiimide group-containing compound having a carbodiimide group introduced into the molecule (polyvalent carbodiimide), a urea group-containing compound such as a urea derivative, an amino group-containing high molecular weight body having an amino group introduced into the molecule, an aziridine group-containing compound having an aziridine group introduced into the molecular terminal (2,2-bis(hydroxymethyl)butanol tris[3-(1-aziridine)propionate]), etc. Among these, from the viewpoint of improving the adhesion between the surface-modified fiber and the rubber, a cyanocyanate-containing compound obtained by reacting a blocked isocyanate compound with an epoxy compound is preferred. From the viewpoint of reducing environmental burden, the oxazolidinone-based compound preferably contains Azoline compounds.

[0054] From the viewpoint of improving the adhesion to rubber, the surface modification layer preferably covers the entire surface of the fiber, but it is sufficient to substantially cover at least a portion of the surface of the fiber. The specific amount of the surface modification layer covering the surface of the fiber is preferably 0.01 to 5.0 parts by mass, more preferably 0.05 to 1.0 parts by mass, and further preferably 0.1 to 0.3 parts by mass, relative to 100 parts by mass of the fiber used as a raw material.

[0055] <Fiber>

[0056] The fiber used for the surface modified fiber of the present invention is not particularly limited, and hydrophobic fibers formed by hydrophobic resins that cannot be firmly bonded to rubber in the prior art can be appropriately used. Since hydrophobic fibers generally do not have polar functional groups on the fiber surface, they lack affinity with the bonding components described later and cannot be firmly bonded to rubber. However, by providing a surface modified layer on the fiber surface as in the present invention, even hydrophobic fibers can be firmly bonded to rubber. It should be noted that in the present invention, "fiber" includes not only single fibers and long fibers, but also non-woven fabrics, fabrics, braids, felts, sponges and other forms.

[0057] Examples of hydrophobic fibers that can be used in the present invention include polyolefin fibers such as polyethylene and polypropylene, polyester fibers such as polyethylene terephthalate, and wholly aromatic polyester fibers. Among these, polyester fibers are preferred due to their excellent manufacturing cost, strength, heat resistance, and durability.

[0058] In the present invention, hydrophilic fibers can be used. Examples of hydrophilic synthetic fibers include synthetic fibers composed of a thermoplastic resin having hydrophilic functional groups such as hydroxyl groups, carboxyl groups, sulfonic acid groups, and amino groups, and / or hydrophilic bonds such as amide bonds.

[0059] Specific examples of such thermoplastic resins include polyvinyl alcohol resins, polyamide resins [aliphatic polyamides such as polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 610, polyamide 612, and polyamide 9C (a polyamide formed from nonanediamine and cyclohexanedicarboxylic acid); semi-aromatic polyamides synthesized from aromatic dicarboxylic acids and aliphatic diamines such as polyamide 9T (a polyamide formed from nonanediamine and terephthalic acid); fully aromatic polyamides synthesized from aromatic dicarboxylic acids and aromatic diamines such as poly(p-phenylene terephthalamide), etc.], polyacrylamide resins, etc.

[0060] Among these, polyvinyl alcohol resin and polyamide resin are preferred. Hydrophilic synthetic fibers can be used alone or in combination of two or more. In addition, for these hydrophilic synthetic fibers, in order to further improve the hydrophilicity, a hydrophilic treatment described later can also be further implemented.

[0061] Examples of the hydrophilic natural fibers include natural cellulose fibers such as wood pulp such as kraft pulp, kapok pulp, and non-wood pulp such as straw pulp.

[0062] Examples of the hydrophilic regenerated fiber include regenerated cellulose fibers such as rayon, lyocell fiber, cupra fiber, and cellulose fiber.

[0063] These natural fibers and regenerated fibers can be used alone or in combination of two or more. In addition, for these hydrophilic natural fibers and regenerated fibers, in order to further improve hydrophilicity, a hydrophilization treatment described below can also be further implemented.

[0064] The hydrophilic fiber may be obtained as long as at least the surface thereof is hydrophilic, and may be, for example, a fiber obtained by hydrophilizing the surface of a hydrophobic fiber, a core-sheath type composite fiber having a hydrophobic resin as a core and a hydrophilic resin as a sheath, etc. For examples of the hydrophilic resin constituting the sheath, the description of the hydrophilic synthetic fiber is cited. Examples of the hydrophobic fiber formed of the hydrophobic resin include: the above-mentioned hydrophobic fiber.

[0065] The hydrophilization treatment is not particularly limited as long as it is a treatment that imparts hydrophilic functional groups to the fiber surface chemically or physically. For example, it can be carried out by a method in which the hydrophobic fibers formed from the above-mentioned hydrophobic resin are modified using compounds or derivatives thereof containing hydrophilic functional groups such as isocyanate groups, epoxy groups, hydroxyl groups, amino groups, ether groups, aldehyde groups, carbonyl groups, carboxyl groups and carbamate groups, or by a method in which the surface is modified by electron beam irradiation.

[0066] The hydrophilic fiber used in the present invention is preferably a synthetic fiber or a regenerated fiber from the viewpoint of use as a reinforcing fiber, and among them, preferably at least one fiber selected from polyester fibers, polyamide fibers, polyvinyl alcohol fibers, and regenerated cellulose fibers.

[0067] In addition, in the present invention, the fibers may be used alone or in combination of two or more.

[0068] <Method for producing surface-modified fibers>

[0069] The method for producing the surface-modified fiber of the present invention is not particularly limited, and the fiber can be produced by preparing a solution of the compound constituting the surface-modified layer using water or an organic solvent, allowing the solution to adhere to the fiber, and then drying the fiber by heat treatment or the like.

[0070] The method for attaching the surface modifier solution to the fiber is not particularly limited, and is preferably carried out by one or more selected from dipping, a roll coater, an oiling roller, an oiling guide, nozzle (spray) coating, and brush coating.

[0071] The heat treatment for drying the solution is preferably performed at a treatment temperature of 100 to 250° C. and a treatment time of 0.1 second to 2 minutes. The heat treatment may be performed only once at a specific temperature or twice or more with varying treatment temperature and treatment time.

[0072] The surface modification layer may contain other components besides the above components. Examples of other components include crosslinking agents, acids, bases, inorganic salts, organic salts, pigments, dyes, antioxidants, polymerization initiators, plasticizers, and the like.

[0073] When the surface modified layer contains the above-mentioned other components, from the viewpoint of improving the adhesion to rubber, the content of the other components in the surface modified layer is preferably 20 mass % or less, more preferably 10 mass % or less, and further preferably 5 mass % or less.

[0074] [Reinforcement Fiber]

[0075] The reinforcing fiber of the present invention comprises the surface-modified fiber of the present invention and an adhesive layer covering at least a portion of the surface of the surface-modified fiber and containing a conjugated diene rubber. In the present invention, the surface-modified fiber has a high affinity with the adhesive layer, so that the fiber and the adhesive layer, and the adhesive layer and the rubber can be firmly bonded.

[0076] In the reinforcing fiber of the present invention, the entire surface of the surface-modified fiber may be covered with the adhesive layer, or at least a portion of the surface may be covered with the adhesive layer. For example, the adhesive component may be present in the form of a film or layer.

[0077] It should be noted that even if the adhesive layer in the present invention does not contain formaldehyde that is harmful to the human body and a resin with formaldehyde as a raw material, a reinforcing fiber with excellent adhesion to rubber can be obtained. In the present invention, when the above-mentioned adhesive layer contains a resin with formaldehyde as a raw material, as the resin, for example: resorcinol / formaldehyde resin, phenol / formaldehyde resin, melamine / formaldehyde resin, and their derivatives can be cited. In the above-mentioned adhesive layer, when the above-mentioned formaldehyde component is contained, its content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, further preferably 3 parts by mass or less, further preferably 1 part by mass or less, and particularly preferably substantially free of the above-mentioned formaldehyde component. The formaldehyde content can be measured by using HPLC or the like after extracting the adhesive layer from the reinforcing fiber using a solvent such as toluene.

[0078] <Adhesive layer>

[0079] The adhesive layer in the reinforcing fiber of the present invention is not particularly limited as long as it contains a conjugated diene rubber, and can be formed, for example, by attaching an adhesive component to the surface-modified fiber, the adhesive component comprising a solution obtained by dissolving a conjugated diene rubber in oil, or an emulsion obtained by dispersing a conjugated diene rubber in water. The form of the adhesive layer is specifically described below.

[0080] 〔Conjugated diene rubber〕

[0081] The conjugated diene rubber used in the present invention contains at least a monomer unit derived from a conjugated diene (hereinafter also referred to as a "conjugated diene unit") in the molecule. For example, the conjugated diene rubber preferably contains 50 mol % or more of the monomer units derived from a conjugated diene in all the monomer units in the conjugated diene rubber.

[0082] As the above-mentioned conjugated diene monomer, for example, butadiene, 2-methyl-1,3-butadiene (hereinafter, also referred to as "isoprene"), 2,3-dimethylbutadiene, 2-phenylbutadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 1,3-octadiene, 1,3-cyclohexadiene, 2-methyl-1,3-octadiene, 1,3,7-octatriene, β-farnesene (hereinafter, also referred to as "farnesene"), myrcene, and chloroprene. These conjugated dienes can be used alone or in combination of two or more. From the viewpoint of reactivity during vulcanization, the conjugated diene rubber more preferably has monomer units derived from one or more selected from butadiene, isoprene, and farnesene.

[0083] The conjugated diene rubber used in the present invention may contain units derived from other monomers than the above-mentioned conjugated diene monomers to the extent that adhesion is not impaired. Examples of other monomers include copolymerizable ethylenically unsaturated monomers and aromatic vinyl compounds.

[0084] Examples of the ethylenically unsaturated monomer include olefins such as ethylene, 1-butene, and isobutylene.

[0085] Examples of the aromatic vinyl compound include styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 4-tert-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, 2,4,6-trimethylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylanthracene, N,N-diethyl-4-aminoethylstyrene, vinylpyridine, 4-methoxystyrene, monochlorostyrene, dichlorostyrene, and divinylbenzene. These aromatic vinyl compounds may be used alone or in combination of two or more.

[0086] When the conjugated diene rubber contains monomer units derived from a monomer other than the conjugated diene monomer, the content thereof is preferably 30 mol % or less, more preferably 10 mol % or less, and even more preferably 5 mol % or less.

[0087] The conjugated diene rubber used in the present invention is preferably a modified conjugated diene rubber having a hydrogen-bonding functional group in a part of the conjugated diene rubber, and more preferably a modified conjugated diene rubber having a conjugated diene unit in at least a part of the polymer chain and having a hydrogen-bonding functional group in the side chain or at the end of the polymer chain.

[0088] When the modified conjugated diene rubber is used as the conjugated diene rubber, the modified conjugated diene rubber interacts with the rubber and the surface-modified fiber as the adherend, thereby bonding the two. When the modified conjugated diene rubber and the adherend rubber are vulcanized to form a covalent bond, a strong cohesive force is generated, thereby further improving the adhesion.

[0089] It is also considered that the hydrogen-bonding functional groups contained in the modified conjugated diene rubber form hydrogen bonds with the surface-modified layer of the surface-modified fiber, thereby improving the adhesiveness.

[0090] It should be noted that in this specification, "hydrogen bond" refers to a bonding interaction formed between a positively polarized hydrogen atom (donor) and a negatively polarized atom (acceptor) having a lone pair of electrons, which is bonded to an atom with high electronegativity (O, N, S, etc.).

[0091] In the present invention, "hydrogen bonding functional group" refers to a functional group that can function as a donor and an acceptor in the above hydrogen bond. Specifically, it can be cited: hydroxyl, epoxy, ether, thiol, carboxyl, carbonyl, aldehyde, amino, imino, imidazole, carbamate, amide, urea, isocyanate, nitrile, silanol and their derivatives. As a derivative of the aldehyde group, its acetalization can be cited. As a derivative of the carboxyl group, its salt, its esterification, its amide, and its acid anhydride can be cited. As a derivative of the silanol group, its esterification can be cited. In addition, as a carboxyl group, it can be cited: a group derived from a monocarboxylic acid and a group derived from a dicarboxylic acid. Among these, it is preferably selected from hydroxyl, epoxy, aldehyde, acetalization of aldehyde, carboxyl, salt of carboxyl, esterification of carboxyl, acid anhydride of carboxyl, silanol, esterification of silanol, amino, imidazole, and thiol. One or more.

[0092] Among these, from the viewpoint of improving adhesion and the viewpoint of easiness in manufacturing the conjugated diene rubber, preferably, one or more selected from the group consisting of a hydroxyl group, a carboxyl group, a carbonyl group, a salt of a carboxyl group, an esterified product of a carboxyl group, and an anhydride of a carboxyl group are preferred; more preferably, one or more selected from the group consisting of a carboxyl group, an esterified product of a carboxyl group, and an anhydride of a carboxyl group are more preferred; and further preferably, an esterified product of maleic anhydride and a functional group derived from maleic anhydride are preferred.

[0093] From the viewpoint of obtaining reinforcing fibers having excellent rubber adhesion, the number of hydrogen-bonding functional groups in the modified conjugated diene rubber is preferably 1 or more per molecule, more preferably 3 or more, and even more preferably 4 or more. From the viewpoint of controlling the viscosity of the modified conjugated diene rubber to an appropriate range and improving the workability, the number of hydrogen-bonding functional groups is preferably 80 or less per molecule, more preferably 40 or less, even more preferably 30 or less, even more preferably 20 or less, and even more preferably 15 or less.

[0094] The average number of hydrogen-bonding functional groups per molecule of the modified conjugated diene rubber is calculated based on the following formula from the equivalent weight (g / eq) of the hydrogen-bonding functional groups of the modified conjugated diene rubber and the number average molecular weight Mn converted to styrene. The equivalent weight of the hydrogen-bonding functional groups of the modified conjugated diene rubber refers to the mass of the conjugated diene bonded to each hydrogen-bonding functional group and other monomers other than the conjugated diene as required.

[0095] Average number of hydrogen-bonding functional groups per molecule = [(number average molecular weight (Mn)) / (molecular weight of styrene unit) × (average molecular weight of conjugated diene and other monomer units other than conjugated diene as required)] / (equivalent weight of hydrogen-bonding functional groups)

[0096] In addition, the calculation method of the equivalent of the hydrogen-bonding functional group can be appropriately selected according to the type of the hydrogen-bonding functional group.

[0097] Examples of methods for obtaining the modified conjugated diene rubber include a method of obtaining the rubber by adding a modifying compound to a polymer of a conjugated diene monomer (hereinafter also referred to as "production method (1)"), a method of obtaining the rubber by oxidizing a conjugated diene polymer (hereinafter also referred to as "production method (2)"), a method of obtaining the rubber by copolymerizing a conjugated diene monomer and a radical polymerizable compound having a hydrogen-bonding functional group (hereinafter also referred to as "production method (3)"), and a method of adding a modifying compound that reacts with a polymerization-active terminal to a polymer of an unmodified conjugated diene monomer having a polymerization-active terminal before adding a polymerization terminator (hereinafter also referred to as "production method (4)"). Among these, from the viewpoint of productivity, the rubber is preferably produced by production method (1), (2) or (3), more preferably by production method (1) or (3), and even more preferably by production method (1).

[0098] [Method for producing modified conjugated diene rubber (1)]

[0099] The production method (1) is a method of adding a modifying compound to a polymer of a conjugated diene monomer, that is, an unmodified conjugated diene rubber (hereinafter also referred to as "unmodified conjugated diene rubber").

[0100] The unmodified conjugated diene rubber can be obtained by polymerizing a conjugated diene and, if necessary, other monomers other than the conjugated diene, for example, by an emulsion polymerization method or a solution polymerization method.

[0101] As the solution polymerization method, a known method or a method based on a known method can be applied. For example, a monomer containing a given amount of conjugated diene is polymerized in the presence of a polar compound in a solvent using a Ziegler catalyst, a metallocene catalyst, an active metal or an active metal compound capable of anionic polymerization.

[0102] Examples of the solvent include aliphatic hydrocarbons such as n-butane, n-pentane, isopentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; and aromatic hydrocarbons such as benzene, toluene, and xylene.

[0103] Examples of active metals capable of anionic polymerization include alkali metals such as lithium, sodium, and potassium; alkaline earth metals such as beryllium, magnesium, calcium, strontium, and barium; and lanthanum-based rare earth metals such as lanthanum and neodymium. Among these active metals capable of anionic polymerization, alkali metals and alkaline earth metals are preferred, and alkali metals are more preferred.

[0104] As the active metal compound capable of anionic polymerization, an organic alkali metal compound is preferred. Examples of the organic alkali metal compound include organic monolithium compounds such as methyl lithium, ethyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, hexyl lithium, phenyl lithium, stilbene lithium, etc.; polyfunctional organic lithium compounds such as dilithium methane, dilithium naphthalene, 1,4-dilithium butane, 1,4-dilithium-2-ethylcyclohexane, 1,3,5-trilithium benzene; sodium naphthalene, potassium naphthalene, etc. Among these organic alkali metal compounds, organic lithium compounds are preferred, and organic monolithium compounds are more preferred.

[0105] The amount of the organic alkali metal compound used can be appropriately set depending on the melt viscosity and molecular weight of the desired unmodified conjugated diene rubber and modified conjugated diene rubber, and is usually 0.01 to 3 parts by mass based on 100 parts by mass of all monomers including conjugated dienes.

[0106] The above-mentioned organic alkali metal compound can also be reacted with a secondary amine such as dibutylamine, dihexylamine, dibenzylamine, etc. to prepare an organic alkali metal amide for use.

[0107] Polar compounds are usually used in anionic polymerization to adjust the microstructure of the conjugated diene site without deactivating the reaction. Examples of polar compounds include ether compounds such as dibutyl ether, tetrahydrofuran, ethylene glycol diethyl ether, and 2,2-di(2-tetrahydrofuranyl)propane; tertiary amines such as tetramethylethylenediamine and trimethylamine; alkali metal alkoxides, phosphine compounds, etc. Polar compounds are usually used in an amount of 0.01 to 1000 moles relative to the organic alkali metal compound.

[0108] The temperature of solution polymerization is usually in the range of -80 to 150° C., preferably in the range of 0 to 100° C., and more preferably in the range of 10 to 90° C. The polymerization method may be either a batch method or a continuous method.

[0109] The polymerization reaction can be stopped by adding a polymerization inhibitor. Examples of the polymerization inhibitor include alcohols such as methanol and isopropanol. The obtained polymerization reaction liquid is injected into a poor solvent such as methanol to precipitate the polymer, or the polymerization reaction liquid is washed with water and separated and then dried, thereby separating the unmodified conjugated diene rubber.

[0110] As a method for producing the unmodified conjugated diene rubber, among the above methods, the solution polymerization method is preferred.

[0111] As the emulsion polymerization method, a known method or a method based on a known method can be applied. For example, a monomer containing a given amount of conjugated diene is emulsified and dispersed in the presence of an emulsifier, and emulsion polymerization is carried out using a radical polymerization initiator.

[0112] Examples of the emulsifier include long-chain fatty acid salts and citronellal salts having at least 10 carbon atoms. Examples of long-chain fatty acid salts include potassium or sodium salts of fatty acids such as capric acid, lauric acid, myristic acid, palmitic acid, oleic acid, and stearic acid.

[0113] As the dispersion solvent, water is usually used, but a water-soluble organic solvent such as methanol or ethanol may be contained within a range not to impair the stability during polymerization.

[0114] Examples of the radical polymerization initiator include persulfates such as ammonium persulfate and potassium persulfate, organic peroxides, and hydrogen peroxide.

[0115] In order to adjust the molecular weight of the obtained unmodified conjugated diene rubber, a chain transfer agent may be used. Examples of the chain transfer agent include mercaptans such as tert-dodecyl mercaptan and n-dodecyl mercaptan; carbon tetrachloride, thioglycolic acid, diterpene, terpinolene, γ-terpinene, α-methylstyrene dimer, and the like.

[0116] The temperature of the emulsion polymerization can be appropriately set depending on the type of radical polymerization initiator to be used, and is usually in the range of 0 to 100° C., preferably in the range of 0 to 60° C. The polymerization method may be either continuous polymerization or batch polymerization.

[0117] The polymerization reaction can be stopped by adding a polymerization inhibitor. Examples of the polymerization inhibitor include amine compounds such as isopropylhydroxylamine, diethylhydroxylamine, and hydroxylamine, quinone compounds such as hydroquinone and benzoquinone, and sodium nitrite.

[0118] After the polymerization reaction stops, an anti-aging agent can be added as required. After the polymerization reaction stops, unreacted monomers are removed as required from the obtained latex, followed by using salts such as sodium chloride, calcium chloride, potassium chloride as coagulants, adding acids such as nitric acid and sulfuric acid as required to adjust the pH of the coagulation system to a given value, while the polymer is coagulated, and then the dispersion solvent is separated to reclaim the polymer. Then, by drying after washing and dehydration, unmodified conjugated diene rubber is obtained. It should be noted that, when coagulating, latex can be mixed with the filler oil made into an emulsified dispersion liquid in advance as required, and recovered as an oil-filled unmodified conjugated diene rubber.

[0119] (Modifying compound used in production method (1))

[0120] The modified compound used in the manufacturing method (1) is not particularly limited. From the viewpoint of improving the adhesion of the reinforcing fiber, a modified compound having a hydrogen-bonding functional group is preferably used. As the hydrogen-bonding functional group, the same functional groups as above can be cited. Among these, from the viewpoint of the strength of the hydrogen bonding force, amino, imidazole, urea, hydroxyl, epoxy, mercapto, silanol, aldehyde, carboxyl and derivatives thereof are preferred. As a derivative of the carboxyl group, a salt thereof, an esterified form thereof, an amidated form thereof, or an anhydride thereof is preferably used. One of these modified compounds having a hydrogen-bonding functional group can be used alone, or two or more can be used in combination.

[0121] Examples of the modified compound include unsaturated carboxylic acids such as maleic acid, fumaric acid, citraconic acid, and itaconic acid; unsaturated carboxylic anhydrides such as maleic anhydride, citraconic anhydride, 2,3-dimethylmaleic anhydride, and itaconic anhydride; unsaturated carboxylic acid esters such as maleate, fumarate, citraconic acid ester, and itaconic acid ester; unsaturated carboxylic acid amides such as maleic acid amide, fumaric acid amide, citraconic acid amide, and itaconic acid amide; unsaturated carboxylic acid imides such as maleic acid imide, fumaric acid imide, citraconic acid imide, and itaconic acid imide; vinyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, mercaptomethyl Silane compounds such as 2-mercaptoethyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, 2-mercaptoethylmethoxydimethylsilane, 2-mercaptoethylethoxydimethylsilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyldimethoxymethylsilane, 3-mercaptopropyldiethoxymethylsilane, 3-mercaptopropyldimethoxyethylsilane, 3-mercaptopropyldiethoxyethylsilane, 3-mercaptopropylmethoxydimethylsilane, and 3-mercaptopropylethoxydimethylsilane.

[0122] The amount of the modifying compound used is preferably 0.1 to 100 parts by mass, more preferably 0.5 to 50 parts by mass, and even more preferably 1 to 30 parts by mass, based on 100 parts by mass of the unmodified conjugated diene rubber.

[0123] The reaction temperature is usually preferably in the range of 0 to 200°C, more preferably in the range of 50 to 200°C.

[0124] In addition, after the above-mentioned modifying compound is grafted onto the unmodified conjugated diene rubber and a hydrogen-bonding functional group is introduced, a modifying compound that can react with the functional group can be further added to introduce other hydrogen-bonding functional groups into the polymer. Specifically, for example, a method can be mentioned in which maleic anhydride is grafted onto the unmodified conjugated diene rubber obtained by living anionic polymerization, and then a compound having a hydroxyl group such as 2-hydroxyethyl methacrylate, methanol, water, etc. is reacted.

[0125] The amount of the modified compound added to the modified conjugated diene rubber is preferably 0.5 to 40 parts by mass, more preferably 1 to 30 parts by mass, and even more preferably 1.5 to 20 parts by mass, relative to 100 parts by mass of the unmodified conjugated diene rubber. It should be noted that the amount of the modified compound added to the modified conjugated diene rubber can be calculated based on the acid value of the modified compound, and can also be obtained by various analytical instruments such as infrared spectroscopy and nuclear magnetic resonance spectroscopy.

[0126] The method for adding the above-mentioned modified compound to the unmodified conjugated diene rubber is not particularly limited, and examples thereof include adding liquid unmodified conjugated diene rubber and one or more modified compounds selected from unsaturated carboxylic acids, unsaturated carboxylic acid derivatives, and silane compounds, and further adding a free radical generator as required, and heating in the presence or absence of an organic solvent. The free radical initiator to be used is not particularly limited, and commercially available organic peroxides, azo compounds, hydrogen peroxide, etc. can be used.

[0127] Examples of the organic solvent used in the above method generally include hydrocarbon solvents and halogenated hydrocarbon solvents. Among these organic solvents, hydrocarbon solvents such as n-butane, n-hexane, n-heptane, cyclohexane, benzene, toluene, and xylene are preferred.

[0128] In addition, when the addition-modified compound is reacted by the above method, an anti-aging agent may be added from the viewpoint of suppressing side reactions. The anti-aging agent may be a commercially available agent, for example, butylated hydroxytoluene (BHT), N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (NOCRAC 6C), etc.

[0129] The amount of the antioxidant added is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the unmodified conjugated diene rubber. When the amount of the antioxidant added is within the above range, side reactions can be suppressed and the modified conjugated diene rubber can be obtained in good yield.

[0130] [Physical properties of conjugated diene rubber]

[0131] The weight average molecular weight (Mw) of the conjugated diene rubber is not particularly limited. From the viewpoint of improving adhesion, it is preferably more than 2000, more preferably 5000 or more, further preferably 10000 or more, further preferably 15000 or more, further preferably 20000 or more, and particularly preferably 25000 or more. From the viewpoint of operability, it is preferably 120000 or less, more preferably 100000 or less, further preferably 75000 or less, and further preferably 55000 or less.

[0132] The number average molecular weight (Mn) of the conjugated diene rubber is not particularly limited. From the viewpoint of improving adhesion, it is preferably 2000 or more, more preferably 5000 or more, further preferably 10000 or more, further preferably 15000 or more, further preferably 20000 or more, and particularly preferably 25000 or more. From the viewpoint of operability, it is preferably 120000 or less, more preferably 75000 or less, further preferably 50000 or less, and further preferably 47000 or less.

[0133] Mw and Mn of the conjugated diene rubber are weight average molecular weight and number average molecular weight in terms of polystyrene determined by gel permeation chromatography (GPC), and can be specifically measured by the method described in Examples.

[0134] The molecular weight distribution (Mw / Mn) of the conjugated diene rubber is preferably 1.00 to 5.00, more preferably 1.00 to 3.00, further preferably 1.00 to 2.00, further preferably 1.00 to 1.50, and particularly preferably 1.00 to 1.30. When Mw / Mn is within the above range, the viscosity deviation of the conjugated diene rubber is small and the handling is easy. The molecular weight distribution (Mw / Mn) refers to the ratio of the weight average molecular weight (Mw) converted to standard polystyrene obtained by GPC measurement / the number average molecular weight (Mn).

[0135] Furthermore, from the viewpoint of the adhesiveness between the conjugated diene rubber and the fiber, the conjugated diene rubber is preferably in a liquid state.

[0136] In this specification, "liquid" means that the melt viscosity of the conjugated diene rubber measured at 38°C is 4000 Pa·s or less. From the viewpoint of improving adhesion, the melt viscosity is preferably 0.1 Pa·s or more, more preferably 1 Pa·s or more, further preferably 10 Pa·s or more, further preferably 30 Pa·s or more, and further preferably 50 Pa·s or more. From the viewpoint of operability, it is preferably 2500 Pa·s or less, more preferably 2100 Pa·s or less. When the melt viscosity is within the above range, the adhesion of the conjugated diene rubber can be improved and the operability can be improved.

[0137] In addition, the melt viscosity of the conjugated diene rubber means the viscosity measured at 38°C using a Brookfield viscometer (B-type viscometer).

[0138] The glass transition temperature (Tg) of the conjugated diene rubber may vary depending on the vinyl content of the conjugated diene unit, the type of the conjugated diene, the content of units derived from other monomers other than the conjugated diene, etc., and is preferably -100 to 10° C., more preferably -100 to 0° C., and even more preferably -100 to -10° C. When Tg is within the above range, high viscosity can be suppressed, and handling becomes easy.

[0139] The vinyl content of the conjugated diene rubber is preferably 80 mol% or less, more preferably 50 mol% or less, and even more preferably 30 mol% or less. When the vinyl content is within the above range, the adhesiveness is improved.

[0140] In this specification, the "vinyl content" refers to the total mole % of conjugated diene units bonded in a 1,2-bond or 3,4-bond manner (conjugated diene units bonded in a manner other than 1,4-bond) in the total 100 mol % of conjugated diene units contained in the modified liquid diene rubber. The vinyl content can be expressed as 1 H-NMR is calculated based on the integrated value ratio of the signal derived from the conjugated diene units bonded together in a 1,2-bond or 3,4-bond manner and the signal derived from the conjugated diene units bonded together in a 1,4-bond manner.

[0141] 〔Oil〕

[0142] The adhesive layer in the present invention can be formed, for example, by applying an adhesive component containing a solution in which a conjugated diene rubber is dissolved in oil to the surface-modified fiber.

[0143] In the present invention, for example, it is preferred to use a so-called non-volatile oil having a vapor pressure of 10 Pa or less at 20°C. By using such an oil, even after the adhesive component is applied to the surface of the fiber, the oil does not volatilize for a long time, so that it is difficult to form coating spots of the adhesive component, and the adhesiveness is improved. In addition, it is possible to suppress the contamination of the manufacturing equipment during the manufacturing process. From these viewpoints, as the oil, the vapor pressure of the oil at 20°C is preferably 8 Pa or less, more preferably 5 Pa or less, further preferably 1 Pa or less, further preferably 0.1 Pa or less, and further preferably 0.01 Pa or less.

[0144] In addition, in this invention, the vapor pressure of oil at 20 degreeC means the value calculated from the optimal curve obtained by applying Antoine's formula to the measured value measured by the gas flow method.

[0145] In the present invention, when oil is used, a heating step for resinization is not required compared to the prior art using RFL, and an evaporation step for removing water or the like is not required compared to the prior art using a solvent such as water as a diluent. As a result, efficient production can be performed with simpler equipment than before, and it is also environmentally friendly.

[0146] The oil having a vapor pressure of 10 Pa or less at 20° C. that can be used in the present invention is not particularly limited as long as it is compatible with the conjugated diene rubber, and examples thereof include natural oils and synthetic oils. Examples of natural oils include mineral oils and vegetable oils.

[0147] Examples of the mineral oil include paraffinic mineral oils, aromatic mineral oils, and naphthenic mineral oils obtained by conventional purification methods such as solvent purification and hydrogenation purification, waxes produced by the Fischer-Tropsch process (GTL wax), and mineral oils produced by isomerizing wax.

[0148] Examples of commercially available paraffin-based mineral oils include "Diana Process Oil" series manufactured by Idemitsu Kosan Co., Ltd. and "Super Oil" series manufactured by JX Energy Co., Ltd.

[0149] Examples of the vegetable oil include linseed oil, camellia oil, macadamia oil, corn oil, mink oil, olive oil, avocado oil, sasanqua oil, castor oil, safflower oil, jojoba oil, sunflower oil, almond oil, rapeseed oil, sesame oil, soybean oil, peanut oil, cottonseed oil, coconut oil, palm kernel oil, and rice bran oil.

[0150] As synthetic oil, hydrocarbon synthetic oil, ester synthetic oil, ether synthetic oil, etc. can be cited. As hydrocarbon synthetic oil, polybutene, polyisobutene, 1-octene oligomer, 1-decene oligomer, and ethylene-propylene copolymer, etc., alpha-olefin oligomers or their hydrides, alkylbenzenes, and alkylnaphthalene, etc. can be cited. As ester synthetic oil, triglycerol fatty acid ester, diglycerol fatty acid ester, monoglycerol fatty acid ester, monohydric alcohol fatty acid ester, polyol fatty acid ester, etc. can be cited. As ether synthetic oil, polyoxyalkylene glycol and polyphenyl ether, etc. can be cited. As commercial products of synthetic oil, "LINEALENE" series manufactured by Idemitsu Kosan Co., Ltd., "FGC32", "FGC46", "FGC68" manufactured by ANDEROL, etc. can be cited.

[0151] As the oil, one selected from the above-mentioned natural oils and synthetic oils may be used, or two or more natural oils, two or more synthetic oils, or one or more each of the natural oils and the synthetic oils may be mixed.

[0152] In the present invention, from the viewpoint of adjusting the viscosity of the adhesive component to an appropriate range and improving workability, mineral oil is preferred, and at least one selected from paraffin-based mineral oils and naphthenic mineral oils is more preferred.

[0153] From the viewpoint of safety, the flash point of the oil used in the present invention is preferably 70° C. or higher. From this viewpoint, the flash point of the oil is preferably 100° C. or higher, more preferably 130° C. or higher, and even more preferably 140° C. or higher. The upper limit of the flash point of the oil is not particularly limited, but is preferably 320° C. or lower.

[0154] From the viewpoint of improving the adhesive force with rubber, the content of the conjugated diene rubber in the above-mentioned adhesive component is preferably 1% by mass or more, more preferably 5% by mass or more, further preferably 10% by mass or more, and preferably 80% by mass or less, more preferably 60% by mass or less, further preferably 50% by mass or less, and further preferably 40% by mass or less. When the content of the conjugated diene rubber in the adhesive component is within the above-mentioned range, sufficient adhesive force can be obtained, and the viscosity of the adhesive component can be prevented from becoming extremely high.

[0155] In addition, the oil content in the above-mentioned adhesive component is preferably 20 mass% or more, more preferably 40 mass% or more, further preferably 50 mass% or more, further preferably 60 mass% or more, and is preferably 99 mass% or less, more preferably 95 mass% or less, further preferably 90 mass% or less.

[0156] The mass ratio of the conjugated diene rubber to the oil in the adhesive component [conjugated diene rubber (R): oil (O)] is preferably 0.1:9.9 to 8:2, more preferably 0.5:9.5 to 6:4, further preferably 1:9 to 5:5, and further preferably 1:9 to 4:6. Generally, it is known that oil deteriorates the adhesiveness of rubber, but when the conjugated diene rubber and the oil are mixed and used in the above-mentioned specific mass ratio, the viscosity can be reduced while maintaining the adhesiveness, the workability of the adhesive component is improved, and the workability of attaching to the surface-modified fiber is also improved.

[0157] In the present invention, the adhesive layer can be formed by attaching an adhesive component containing an emulsion in which the conjugated diene rubber is dispersed in water to the surface-modified fiber.

[0158] When the conjugated diene rubber is dispersed in water to form an oil-in-water emulsion, it is preferred to prepare an emulsion (latex) of the adhesive component in advance by a mechanical or chemical method and use it at a given concentration by dilution or the like.

[0159] Examples of mechanical methods include methods using a homogenizer, a high-speed stirrer, a disperser, a colloid mill, a pipeline mixer, a high-pressure homogenizer, an ultrasonic emulsifier, and the like. These may be used alone or in combination.

[0160] As chemical methods, various methods such as reverse emulsification method, D phase emulsification method, HLB temperature emulsification method, gel emulsification method and liquid crystal emulsification method can be mentioned. From the viewpoint of obtaining an emulsion with a small particle size in a simple manner, the reverse emulsification method is preferred. In addition, in order to obtain an emulsion with a small particle size, it is sometimes preferred to heat the modified conjugated diene rubber at an appropriate temperature (e.g., 30 to 80° C.) to reduce the viscosity of the modified conjugated diene rubber.

[0161] From the viewpoint of improving the adhesive force with rubber, when the adhesive component is made into an emulsion, the content of the conjugated diene rubber in the adhesive component is preferably 0.5% by mass or more, more preferably 1% by mass or more, and further preferably 2% by mass or more, and preferably 60% by mass or less, more preferably 40% by mass or less, further preferably 30% by mass or less, and further preferably 20% by mass or less. When the content of the conjugated diene rubber in the adhesive component is within the above range, sufficient adhesive force can be obtained, and the viscosity of the adhesive component can be prevented from becoming extremely high.

[0162] The conjugated diene rubber may be used alone or in combination of two or more thereof. The oil may be used alone or in combination of two or more thereof.

[0163] Furthermore, the adhesive component in the present invention may contain other components besides the conjugated diene rubber and the oil within a range that does not inhibit the adhesive force with the rubber.

[0164] Examples of the other components include other polymers (for example, unmodified conjugated diene rubber), acids, bases, antioxidants, curing agents, dispersants, pigments, dyes, adhesion promoters, carbon black, and the like.

[0165] When the above-mentioned adhesive component contains other components, the content thereof is preferably 10,000 parts by mass or less, more preferably 1,000 parts by mass or less, further preferably 100 parts by mass or less, further preferably 50 parts by mass or less, further preferably 25 parts by mass or less, and further more preferably 10 parts by mass or less, relative to 100 parts by mass of the conjugated diene rubber.

[0166] [Method for producing reinforcing fiber]

[0167] The method for producing the reinforcing fiber of the present invention is not particularly limited, and the reinforcing fiber can be produced by a method including the steps of causing the conjugated diene rubber to adhere to the fiber in a state mixed with the oil or causing the conjugated diene rubber to adhere to the fiber in a state dispersed in water.

[0168] In the present invention, from the viewpoint of efficiently attaching the conjugated diene rubber to the surface-modified fiber and from the viewpoint of suppressing contamination of the production equipment, a method including the step of attaching the conjugated diene rubber to the fiber in a state mixed with the oil is preferred.

[0169] As a more specific method for producing the reinforcing fiber of the present invention, the following method can be mentioned.

[0170] [Method (I)]

[0171] The method (I) is not particularly limited as long as it is a method of forming an adhesive layer containing the above-mentioned adhesive component on the surface of the surface-modified fiber, but from the viewpoint of improving the adhesion to rubber, a method including the following step I-1 is preferred.

[0172] Step I-1: Step of attaching the above-mentioned adhesive component to the surface of the surface-modified fiber

[0173] In step I-1, the method for attaching the adhesive component to the surface-modified fiber is not particularly limited, and examples thereof include a method of directly attaching the adhesive component and a method of attaching the adhesive component by adding a solvent as needed.

[0174] As a method for attaching the adhesive component, it is preferable to use one or more selected from the group consisting of dipping, a roll coater, an oiling roller, an oiling guide, nozzle (spray) coating, and brush coating.

[0175] From the viewpoint of improving the adhesion between the reinforcing fibers and the rubber, the adhesion amount of the above-mentioned adhesive component is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and further preferably 1 part by mass or more, relative to 100 parts by mass of the fibers used as the raw material, and from the viewpoint of the balance between the manufacturing cost and the effect, it is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and further preferably 3 parts by mass or less.

[0176] In the present invention, when a conjugated diene rubber is used in combination with a specific oil, the reinforcing fiber of the present invention can be obtained by attaching an adhesive component to the surface-modified fiber and then fusing the fiber at room temperature of about 20° C. for about 3 to 10 days. However, the following step I-2 may be performed depending on the situation.

[0177] Step I-2: Step of heat-treating the surface-modified fiber to which the adhesive component obtained in step I-1 is attached

[0178] The heat treatment in step I-2 is preferably performed at a treatment temperature of 100 to 200° C. for a treatment time of 0.1 second to 2 minutes. The conjugated diene rubber contained in the above-mentioned adhesive component has reactive multiple bonds, and therefore, the heat treatment in the presence of oxygen is preferably performed at 200° C. or less, more preferably 175° C. or less. When the temperature of the heat treatment is within the above-mentioned range, the adhesive force can be improved without reducing the amount of reactive multiple bonds in the conjugated diene rubber, and further, the deterioration of the fiber can be suppressed, and the quality of coloring, etc. can be improved.

[0179] The reinforcing fiber may contain other components besides the surface-modified fiber and the adhesive component. Examples of other components include crosslinking agents, acids, bases, inorganic salts, organic salts, pigments, dyes, antioxidants, polymerization initiators, plasticizers, and the like.

[0180] From the viewpoint of improving the adhesion to rubber and reinforcing the strength, the total content of the hydrophilic fiber and the adhesive component in the reinforcing fiber is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.

[0181] <Physical properties of reinforcing fibers>

[0182] The reinforcing fiber is preferably a multifilament with a single yarn fineness of 0.1 dtex or more and 30 dtex or less. The single yarn fineness may be less than 0.1 dtex, but from the perspective of the ease of industrial production, it is preferably 0.1 dtex or more. In addition, when the single yarn fineness is 30 dtex or less, the surface area of ​​the fiber increases when it is made into a reinforcing fiber, so the adhesion to the rubber is improved. From this point of view, the reinforcing fiber of the present invention is preferably a multifilament with a single yarn fineness of more than 0.3 dtex, more preferably more than 0.5 dtex, more preferably more than 1 dtex, and more preferably less than 20 dtex, more preferably less than 15 dtex, and more preferably less than 10 dtex.

[0183] The rubber adhesion of the reinforcing fiber of the present invention is preferably 30 N / 25.4 mm or more, more preferably 50 N / 25.4 mm or more, further preferably 70 N / 25.4 mm or more, and further preferably 80 N / 25.4 mm or more, and is usually 200 N / 25.4 mm or less. When the rubber adhesion of the reinforcing fiber is above the above lower limit, a fabric, a braided fabric, and a molded body having excellent reinforcement strength can be obtained.

[0184] In addition, the rubber adhesion of the reinforcing fiber of the present invention is preferably 30N / 3 or more, more preferably 40N / 3 or more, further preferably 50N / 3 or more, and further preferably 60N / 3 or more, and is usually 200N / 3 or less. When the rubber adhesion of the reinforcing fiber is above the above lower limit, a fabric, a braided fabric, and a molded body having excellent reinforcement strength can be obtained.

[0185] It should be noted that the rubber adhesion of the reinforcing fibers can be measured by the method described in the Examples.

[0186] The reinforcing fiber of the present invention can be used in any form, preferably in the form of a fiber cord, a woven fabric, a braid, etc. containing the reinforcing fiber in at least a portion, and more preferably in the form of a woven fabric or a braid containing the reinforcing fiber in at least a portion. For example, it can be used as a braid bonded to rubber as described later. In addition, it can also be used as a reinforcing fiber embedded in a resin, an adhesive, etc.

[0187] [Molding body]

[0188] The molded body of the present invention is not particularly limited as long as the above-mentioned reinforcing fibers are used. Among them, from the viewpoint that the above-mentioned reinforcing fibers have excellent adhesion to rubber, a molded body having the above-mentioned reinforcing fibers and a rubber layer (hereinafter also referred to as a "rubber molded body") is particularly preferred. From the viewpoint of maintaining the shape of the rubber, the reinforcing fibers used in the above-mentioned rubber molded body are preferably used in the form of a fabric or braid containing the reinforcing fibers in at least a portion, and more preferably used in the form of a laminated body formed by laminating a reinforcing layer and a rubber layer, the reinforcing layer being formed by a fabric or braid containing the reinforcing fibers in at least a portion.

[0189] As a preferred embodiment of the molded body of the present invention, it has fibers, a surface modification layer, an adhesive layer, and a rubber layer in sequence, and the adhesion between the adhesive layer and the rubber layer is 70N or more, more preferably 80N or more per an average width of 25.4 mm. When the adhesion is 70N or more, it can be appropriately used for various purposes described later.

[0190] The rubber molded body can be used as a member of a rubber product such as a tire for automobiles, a belt such as a conveyor belt or a timing belt, a tube, and a vibration-proof rubber, and is more preferably used as a tire, a belt, or a tube.

[0191] The above-mentioned automobile tire can be used for various members made of a composite material of reinforcing fiber and rubber component, such as belts, carcass cords, switches, and rim bands.

[0192] The above-mentioned tube can be used for various fluid transport purposes in various applications, for example, it is suitable for fluid transport tubes for automobiles, and is particularly preferably used for automobile liquid fuel tubes, automobile brake oil pipes, and refrigerant pipes, and is more preferably used for automobile brake oil pipes.

[0193] The rubber molded body is preferably molded using the above-mentioned reinforcing fibers and a rubber composition in which a compounding agent commonly used in the rubber field is blended with a rubber component.

[0194] As the rubber component, there is no particular limitation, and examples thereof include: NR (natural rubber), IR (polyisoprene rubber), BR (polybutadiene rubber), SBR (styrene-butadiene rubber), NBR (nitrile rubber), EPM (ethylene-propylene copolymer rubber), EPDM (ethylene-propylene-non-conjugated diene copolymer rubber), IIR (butyl rubber), halogenated butyl rubber, CR (chloroprene rubber), etc. Among them, NR, IR, BR, SBR, EPDM, CR are preferably used, and EPDM is more preferably used. These rubber components can be used alone or in combination of two or more. In tire applications, rubbers commonly used in the tire industry can be used. Among them, it is preferred to use natural rubber alone, or to use natural rubber and SBR in combination. When natural rubber and SBR are combined, from the viewpoint of suppressing the reduction of physical properties caused by vulcanization reversion of rubber, the mass ratio of natural rubber to SBR (natural rubber / SBR) is preferably set in the range of 50 / 50 to 90 / 10.

[0195] Examples of the natural rubber include TSR (Technically Specified Rubber) such as SMR (TSR produced in Malaysia), SIR (TSR produced in Indonesia), and STR (TSR produced in Thailand), natural rubber commonly used in the tire industry such as RSS (Ribbed Smoked Sheet), and modified natural rubbers such as high-purity natural rubber, epoxidized natural rubber, hydroxylated natural rubber, hydrogenated natural rubber, and grafted natural rubber.

[0196] As the above-mentioned SBR, a common SBR used in tire applications can be used, and specifically, an SBR having a styrene content of 0.1 to 70% by mass is preferred, 5 to 50% by mass is more preferred, and 15 to 35% by mass is further preferred. In addition, an SBR having a vinyl content of 0.1 to 60% by mass is preferred, and 0.1 to 55% by mass is more preferred.

[0197] The weight average molecular weight (Mw) of the SBR is preferably 100,000 to 2,500,000, more preferably 150,000 to 2,000,000, and further preferably 200,000 to 1,500,000. In the case of the above range, both processability and mechanical strength can be taken into account. It should be noted that the weight average molecular weight of SBR refers to the weight average molecular weight converted to polystyrene obtained by gel permeation chromatography (GPC).

[0198] As the SBR, a modified SBR having a functional group introduced therein may be used as long as the effects of the present invention are not impaired. Examples of the functional group include an amino group, an alkoxysilyl group, a hydroxyl group, an epoxy group, and a carboxyl group.

[0199] The rubber composition may further contain a filler in addition to the rubber component. Examples of such fillers include inorganic fillers such as carbon black, silica, clay, mica, calcium carbonate, magnesium hydroxide, aluminum hydroxide, barium sulfate, titanium oxide, glass fiber, fibrous filler, and hollow glass spheres; and organic fillers such as resin particles, wood powder, and cork powder. By including such fillers in the rubber composition, physical properties such as mechanical strength, heat resistance, and weather resistance can be improved, hardness can be adjusted, and rubber volume can be increased.

[0200] Among the above-mentioned fillers, carbon black and silica are preferred from the viewpoint of improving physical properties such as increasing mechanical strength.

[0201] Examples of the carbon black include furnace black, channel black, thermal black, acetylene black, and Ketjen black. Among these carbon blacks, furnace black is preferred from the viewpoint of increasing the crosslinking rate and mechanical strength.

[0202] The average particle size of the carbon black is preferably 5 to 100 nm, more preferably 5 to 80 nm, and even more preferably 5 to 70 nm. The average particle size of the carbon black can be obtained by measuring the diameters of the particles using a transmission electron microscope and calculating the average value.

[0203] Examples of the silica include wet silica (hydrous silicic acid), dry silica (anhydrous silicic acid), calcium silicate, aluminum silicate, etc. Among these silicas, wet silica is preferred.

[0204] The average particle size of the silica is preferably 0.5 to 200 nm, more preferably 5 to 150 nm, and even more preferably 10 to 100 nm.

[0205] The average particle size of the silica can be determined by measuring the diameters of the particles using a transmission electron microscope and calculating the average value.

[0206] In the rubber composition, the content of the filler is preferably 20 to 150 parts by mass, more preferably 25 to 130 parts by mass, and even more preferably 25 to 110 parts by mass, based on 100 parts by mass of the rubber component.

[0207] When a filler other than silica and carbon black is used as the filler, the content thereof is preferably 20 to 120 parts by mass, more preferably 20 to 90 parts by mass, and even more preferably 20 to 80 parts by mass, based on 100 parts by mass of the rubber component.

[0208] These fillers may be used alone or in combination of two or more.

[0209] In order to crosslink the rubber component, the rubber composition may further contain a crosslinking agent. Examples of the crosslinking agent include sulfur, sulfur compounds, oxygen, organic peroxides, phenolic resins, amino resins, quinones and quinone dioxime derivatives, halogen compounds, aldehyde compounds, alcohol compounds, epoxy compounds, metal halides and organic metal halides, and silane compounds. These crosslinking agents may be used alone or in combination of two or more. From the perspective of the mechanical properties of the crosslinked product, the crosslinking agent generally contains 0.1 to 10 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.8 to 5 parts by mass, relative to 100 parts by mass of the rubber component.

[0210] For the rubber composition, for example, as a cross-linking agent for cross-linking (vulcanizing) the rubber component, in the case of containing sulfur, sulfur compounds, etc., a vulcanization accelerator may be further contained. As the vulcanization accelerator, for example: guanidine compounds, sulfenamide compounds, thiazole compounds, thuybestrol compounds, thiourea compounds, dithiocarbamic acid compounds, aldehyde-amine compounds, aldehyde-amine compounds, imidazoline compounds, and xanthate compounds, etc., can be cited. These vulcanization accelerators can be used alone or in combination of two or more. Relative to 100 parts by mass of the rubber component, the vulcanization accelerator usually contains 0.1 to 15 parts by mass, preferably 0.1 to 10 parts by mass.

[0211] For the rubber composition, for example, as a crosslinking agent for crosslinking (vulcanizing) the rubber component, in the case of containing sulfur, sulfur compounds, etc., a vulcanizing aid may be further contained. Examples of the vulcanizing aid include fatty acids such as stearic acid, metal oxides such as zinc flower, fatty acid metal salts such as zinc stearate. These vulcanizing aids may be used alone or in combination of two or more. The vulcanizing aid generally contains 0.1 to 15 parts by mass, preferably 1 to 10 parts by mass, relative to 100 parts by mass of the rubber component.

[0212] When the rubber composition contains silica as a filler, it is preferred to further contain a silane coupling agent. Examples of the silane coupling agent include sulfide compounds, mercapto compounds, vinyl compounds, amino compounds, glycidoxy compounds, nitro compounds, and chlorine compounds.

[0213] These silane coupling agents can be used alone or in combination of two or more. The above silane coupling agent preferably contains 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and further preferably 1 to 15 parts by mass relative to 100 parts by mass of silica. When the content of the silane coupling agent is within the above range, the dispersibility, coupling effect, and reinforcement are improved.

[0214] The rubber composition may contain, as necessary, silicone oil, aromatic oil, TDAE (Treated Distilled Aromatic Extracts), MES (Mild Extracted Solvates), RAE (Residual Aromatic Extracts), process oils such as paraffin oil and naphthenic oil, aliphatic hydrocarbon resins, alicyclic hydrocarbon resins, C9 resins, rosin resins, coumarone-indene resins, phenolic resins and other resin components as softeners in order to improve processability, fluidity and the like, within the range not hindering the effects of the present invention. When the rubber composition contains the process oil as a softener, the content thereof is preferably less than 50 parts by mass relative to 100 parts by mass of the rubber component.

[0215] The rubber composition may contain additives such as anti-aging agent, wax, antioxidant, lubricant, light stabilizer, anti-scorch agent, processing aid, pigment, pigment and other coloring agents, flame retardant, antistatic agent, matting agent, anti-blocking agent, ultraviolet absorber, release agent, foaming agent, antibacterial agent, mildewproof agent, fragrance, etc. as needed in order to improve weather resistance, heat resistance, oxidation resistance, etc., within the scope that does not hinder the effect of the present invention. As antioxidant, for example, hindered phenolic compounds, phosphorus compounds, lactone compounds, hydroxyl compounds, etc. may be mentioned. As anti-aging agent, for example, amine-ketone compounds, imidazole compounds, amine compounds, phenolic compounds, sulfur compounds and phosphorus compounds, etc. may be mentioned. These additives may be used alone or in combination of two or more.

[0216] As a method for producing the rubber molded body, for example, the reinforcing fibers are embedded in the unvulcanized rubber composition and the rubber composition is vulcanized to obtain a molded body in which the surface-modified fibers and the rubber component are bonded via the adhesive component.

[0217] Examples of the automobile brake hose include a brake hose having an inner rubber layer and an outer rubber layer, and having one or two reinforcement layers formed of the above-mentioned reinforcing fibers between the inner rubber layer and the outer rubber layer.

[0218] As the rubber components constituting the inner rubber layer and the outer rubber layer, the above components can be cited. Among them, as the rubber component constituting the inner rubber layer, EPDM, SBR, etc. can be cited, and as the rubber component constituting the outer rubber layer, EPDM, CR, etc. can be cited. The above-mentioned reinforcement layer can be formed by weaving reinforcement fibers.

[0219] As a method for manufacturing the brake hose, a reinforcement layer (first reinforcement layer) formed by weaving the reinforcement fibers may be formed on the outer surface of the inner rubber layer. In the case of forming two reinforcement layers, an intermediate rubber layer may be further formed on the outer surface of the first reinforcement layer, and a reinforcement layer (second reinforcement layer) formed by weaving the reinforcement fibers may be formed on the outer surface of the intermediate rubber layer. Therefore, the brake hose may be manufactured by forming an outer rubber layer on the outer surface of a reinforcement layer (first reinforcement layer or second reinforcement layer) and vulcanizing the reinforcement layer.

[0220] The vulcanization temperature can be appropriately selected depending on the types of constituent materials of each layer of the brake hose, but is preferably 200° C. or lower from the viewpoint of suppressing degradation of rubber and reinforcing fibers and improving the adhesive strength between rubber and reinforcing fibers.

[0221] Example

[0222] Hereinafter, the present invention will be described in more detail with reference to Examples and the like, but the present invention is not limited to the Examples and the like.

[0223] <Manufacturing of modified conjugated diene rubber>

[0224] Production of a modified conjugated diene rubber having a monomer unit represented by the following formula (1a):

[0225] [Chemical formula 1]

[0226]

[0227] Production Example 1: Production of modified conjugated diene rubber (A-1)

[0228] The fully dried 5L autoclave was purged with nitrogen, and 756g of hexane and 122.3g of n-butyl lithium (17% by mass hexane solution) were added. After the temperature was raised to 50°C, 1344g of butadiene was gradually added under stirring while controlling the polymerization temperature to 50°C, and the polymerization was carried out for 1 hour. Then, methanol was added to stop the polymerization reaction to obtain a polymer solution. Water was added to the obtained polymer solution and stirred, and the polymer solution was washed with water. After the stirring was terminated and the separation into the polymer solution phase and the water phase was confirmed, the water was separated. The polymer solution after washing was vacuum dried at 70°C for 24 hours to obtain unmodified liquid polybutadiene (A'-1).

[0229] Next, 600 g of the obtained unmodified liquid polybutadiene (A'-1) was added to a 1 L autoclave purged with nitrogen, and 30 g of maleic anhydride and 0.6 g of N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (trade name "NOCRAC6C", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) were added, and the mixture was reacted at 170°C for 24 hours to obtain maleic anhydride-modified liquid polybutadiene (A-1).

[0230] Production Example 2: Production of modified conjugated diene rubber (A-2)

[0231] The fully dried 5L autoclave was purged with nitrogen, and 1260g of hexane and 36.3g of n-butyl lithium (17% by mass hexane solution) were added. After the temperature was raised to 50°C, 1260g of butadiene was gradually added under stirring while controlling the polymerization temperature to 50°C, and the polymerization was carried out for 1 hour. Then, methanol was added to stop the polymerization reaction to obtain a polymer solution. Water was added to the obtained polymer solution and stirred, and the polymer solution was washed with water. After the stirring was terminated and the separation into the polymer solution phase and the aqueous phase was confirmed, the water was separated. The polymer solution after washing was vacuum dried at 70°C for 24 hours to obtain unmodified liquid polybutadiene (A'-2).

[0232] Next, 500 g of the obtained unmodified liquid polybutadiene (A'-2) was added to a 1 L autoclave purged with nitrogen, and 25 g of maleic anhydride and 0.5 g of N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (trade name "NOCRAC6C", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) were added, and the mixture was reacted at 170°C for 24 hours to obtain maleic anhydride-modified liquid polybutadiene (A-2).

[0233] Production Example 3: Production of modified conjugated diene rubber (A-3)

[0234] The fully dried 5L autoclave was purged with nitrogen, and 1140g of hexane and 20.9g of n-butyl lithium (17% by mass hexane solution) were added. After the temperature was raised to 50°C, 1390g of butadiene was gradually added under stirring while controlling the polymerization temperature to 50°C, and the polymerization was carried out for 1 hour. Then, methanol was added to stop the polymerization reaction to obtain a polymer solution. Water was added to the obtained polymer solution and stirred, and the polymer solution was washed with water. After the stirring was terminated and the separation into the polymer solution phase and the water phase was confirmed, the water was separated. The polymer solution after washing was vacuum dried at 70°C for 24 hours to obtain unmodified liquid polybutadiene (A'-3).

[0235] Next, 500 g of the obtained unmodified liquid polybutadiene (A'-3) was added to a 1 L autoclave purged with nitrogen, and 25 g of maleic anhydride and 0.5 g of N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (trade name "NOCRAC6C", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) were added, and the mixture was reacted at 170°C for 24 hours to obtain maleic anhydride-modified liquid polybutadiene (A-3).

[0236] Production Example 4: Production of modified conjugated diene rubber (A-4)

[0237] 9.0 g of methanol was added to 525 g of the obtained maleic anhydride-modified liquid polybutadiene (A-3), and the mixture was reacted at 80° C. for 6 hours to obtain maleic acid monomethyl ester-modified liquid polybutadiene (A-4).

[0238] Production Example 5: Production of modified conjugated diene rubber (A-5)

[0239] 8.5 g of methanol was added to 525 g of the obtained maleic anhydride-modified liquid polybutadiene (A-2), and the mixture was reacted at 80° C. for 6 hours to obtain a maleic acid monomethyl ester-modified liquid polybutadiene (A-5).

[0240] The measuring methods and calculating methods of the physical properties of the modified conjugated diene rubber were as follows. The results are shown in Table 1.

[0241] <Methods for measuring weight average molecular weight, number average molecular weight and molecular weight distribution>

[0242] The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the modified conjugated diene rubber were determined by GPC (gel permeation chromatography) in terms of standard polystyrene. The measuring apparatus and conditions were as follows.

[0243] · Equipment: GPC equipment "GPC8020" manufactured by Tosoh Corporation

[0244] ·Separation column: "TSKgelG4000HXL" manufactured by Tosoh Corporation

[0245] Detector: "RI-8020" manufactured by Tosoh Corporation

[0246] ·Eluent: Tetrahydrofuran

[0247] Eluent flow rate: 1.0ml / min

[0248] Sample concentration: 5mg / 10ml

[0249] Column temperature: 40℃

[0250] <Method for measuring melt viscosity>

[0251] The melt viscosity of the modified conjugated diene rubber at 38° C. was measured using a Brookfield viscometer (manufactured by Brookfield Engineering Labs, Inc.).

[0252] <Method for measuring glass transition temperature>

[0253] 10 mg of the modified conjugated diene rubber was collected in an aluminum pan, and a thermogram was measured by differential scanning calorimetry (DSC) at a temperature increase rate of 10° C. / min. The peak top value of DDSC was defined as the glass transition temperature.

[0254] <Measurement method of vinyl content>

[0255] Made by JEOL Ltd. 1 The vinyl content of the modified conjugated diene rubber was measured by H-NMR (500 MHz) at a concentration of sample / heavy chloroform = 50 mg / 1 mL and a cumulative number of 1024. The vinyl content was calculated from the area ratio of the double bond peak derived from the vinylated diene compound and the double bond peak derived from the unvinylated diene compound in the obtained spectrum.

[0256] <Average number of hydrogen-bonding functional groups per molecule>

[0257] The average number of hydrogen-bonding functional groups per molecule of the modified conjugated diene rubber is calculated by the following formula from the equivalent weight (g / eq) of the hydrogen-bonding functional groups of the modified conjugated diene rubber and the styrene-equivalent number average molecular weight Mn.

[0258] Average number of hydrogen-bonding functional groups per molecule = [(number average molecular weight (Mn)) / (molecular weight of styrene unit) × (average molecular weight of conjugated diene and other monomer units other than conjugated diene as required)] / (equivalent weight of hydrogen-bonding functional groups)

[0259] In addition, the calculation method of the equivalent of the hydrogen-bonding functional group can be appropriately selected according to the type of the hydrogen-bonding functional group.

[0260] The calculation of the average number of hydrogen-bonding functional groups per molecule of maleic anhydride-modified conjugated diene rubber and monomethyl maleate-modified conjugated diene rubber is carried out by determining the acid value of the maleic anhydride-modified conjugated diene rubber and monomethyl maleate-modified conjugated diene rubber and calculating the equivalent weight (g / eq) of the hydrogen-bonding functional groups based on the acid value.

[0261] The sample after the modification reaction was washed 4 times with methanol (5 mL for 1 g of the sample) to remove impurities such as antioxidants, and then dried under reduced pressure at 80°C for 12 hours. 180 mL of toluene and 20 mL of ethanol were added to 3 g of the sample after the modification reaction to dissolve it, and then neutralized and titrated with a 0.1N potassium hydroxide ethanol solution to obtain the acid value using the following formula.

[0262] Acid value (mgKOH / g) = (A-B) × F × 5.611 / S

[0263] A: The amount of 0.1N potassium hydroxide ethanol solution required for neutralization (mL)

[0264] B: Amount of 0.1N potassium hydroxide ethanol solution added to a blank sample containing no sample (mL)

[0265] F: Titer of 0.1N potassium hydroxide in ethanol

[0266] S: The mass of the sample to be weighed (g)

[0267] According to the acid value, the mass of the hydrogen-bonding functional groups contained in the maleic anhydride-modified conjugated diene rubber and the monomethyl maleate-modified conjugated diene rubber per 1 g is calculated using the following formula, and the mass (polymer main chain mass) other than the functional groups contained in the maleic anhydride-modified conjugated diene rubber and the monomethyl maleate-modified conjugated diene rubber per 1 g is further calculated. Then, the equivalent weight (g / eq) of the hydrogen-bonding functional groups is calculated using the following formula.

[0268] [Mass of hydrogen-bonding functional groups per 1 g] = [acid value] / [56.11] × [molecular weight of hydrogen-bonding functional groups] / 1000

[0269] [Mass of polymer backbone per 1g] = 1 - [Mass of hydrogen-bonding functional groups per 1g]

[0270] [Equivalent weight of hydrogen-bonding functional groups] = [Mass of polymer backbone per 1 g] / ([Mass of hydrogen-bonding functional groups per 1 g] / [Molecular weight of hydrogen-bonding functional groups])

[0271] [Table 1]

[0272]

[0273] <Constituent materials of the surface modification layer (surface modifier)>

[0274] By mixing the components according to the formulation shown in Table 2, constituent materials of the surface modification layer (surface modification agents B-1 to B-9) were prepared.

[0275] [Table 2]

[0276]

[0277] The details of the compounds described in Table 2 are as follows.

[0278] Blocked isocyanate compounds

[0279] MEIKANATE DM-3031CONC (produced by Meisei Chemical Industry Co., Ltd., purity 54 mass%)

[0280] Epoxides

[0281] DENACOL EX-614B (manufactured by Nagase ChemteX Co., Ltd., purity 100 mass %)

[0282] Contains Oxazoline compounds

[0283] EPOCROS WS-700 (manufactured by Nippon Shokubai Co., Ltd., purity 25 mass%)

[0284] ·Carbodiimide compounds

[0285] CARBODILITE Prototype (manufactured by Nisshinbo Chemical Co., Ltd., purity 40 mass %)

[0286] Sodium acrylate compounds

[0287] Aqualic DL-453 (manufactured by Nippon Shokubai Co., Ltd., purity 35 mass%)

[0288] ·Ethylenimine compounds

[0289] EPOMIN SP-200 (manufactured by Nippon Shokubai Co., Ltd., purity 100 mass %)

[0290] ·Diamide type cationic compounds

[0291] ADEKA MINE SF-201 (manufactured by ADEKA Corporation, purity 80 mass%)

[0292] <Diluted solution of conjugated diene rubber>

[0293] A solution was prepared by diluting each modified conjugated diene rubber described in Table 1 to 25% by mass using a fatty acid ester or a mineral oil.

[0294] It should be noted that as the fatty acid ester, a polyol fatty acid ester (trimethylolpropane trioctanoate) was used, and its vapor pressure at 20°C was 1.7×10 -7Pa, with a flash point of 258°C and no volatility. In addition, as mineral oil, a 20°C vapor pressure of 7.0×10 -3 Pa, flash point is 158℃, no volatile mineral oil.

[0295] <Example 1>

[0296] PET fibers (total fineness 1100 dtex, single fiber fineness 6.10 dtex) as polyester-based fibers were immersed in the surface modifier (B-1), and the liquid was squeezed with a roll.

[0297] Then, the obtained fibers were dried at 140° C. for 60 seconds and further heat treated at 240° C. for 60 seconds, thereby producing surface-modified fibers.

[0298] Next, a diluted solution of modified conjugated diene rubber was prepared to have the composition and adhesion amount shown in Table 3, and the diluted solution was applied to the surface-modified fiber using an oiling guide and wound up. Then, after fusion at room temperature (20° C.) for 3 days, the fiber was twisted at a twist of 80 T / m to produce a reinforcing fiber.

[0299] <Examples 2 to 7 and Comparative Examples 1 to 4>

[0300] Except having changed the surface modification layer, the adhesive layer, and the adhesion amount thereof as described in Table 3, the reinforcing fiber was produced by the same method as in Example 1.

[0301] <Reference Example 1>

[0302] PET fibers (total fineness 1100 dtex, single fiber fineness 6.10 dtex) as polyester fibers were immersed in the pretreatment liquid described below, applied with roll squeeze, dried at 140°C for 60 seconds, and further heat treated at 240°C for 60 seconds.

[0303] Next, after imparting RFL, the treated yarn was dried at 140°C for 60 seconds and further heat treated at 240°C for 60 seconds to obtain a treated yarn. The treated yarn obtained was twisted at a twist of 80 T / m to produce a reinforcing fiber. It should be noted that the pretreatment liquid and RFL liquid used were prepared by the following method.

[0304] 〔Preparation of RFL pretreatment solution〕

[0305] Water: 96.96 parts by mass

[0306] Blocked isocyanate: 2.29 parts by mass

[0307] Epoxy compound: 0.75 parts by mass

[0308] The pretreatment liquid was prepared using a blocked isocyanate and an epoxy resin. The blocked isocyanate used was "Meikanote DM-3031CONC" manufactured by Meisei Chemical Industry Co., Ltd., and the epoxy resin used was "DENACOL EX-614B" manufactured by Nagase ChemteX Co., Ltd.

[0309] 〔Preparation of RFL liquid〕

[0310] Liquid A

[0311] Water: 524 parts by mass

[0312] Resorcinol: 15 parts by mass

[0313] Formaldehyde (active ingredient 37% by mass): 16 parts by mass

[0314] Sodium hydroxide aqueous solution (active ingredient 10% by mass): 4 parts by mass

[0315] The above-mentioned liquid A was aged at 25°C for 6 hours.

[0316] Liquid B

[0317] SBR latex (active ingredient 40% by mass): 207 parts by mass

[0318] Vinylpyridine modified SBR latex (active ingredient 40% by mass): 233 parts by mass

[0319] The above-mentioned liquid B was mixed with the matured liquid A, and then aged at 25° C. for 16 hours to produce an RFL liquid.

[0320] <Measurement of Zeta Potential>

[0321] The zeta potential of the fiber surface of the surface-modified fibers obtained in Examples 1 to 7 and Comparative Examples 1 to 4 was measured using a zeta potential / particle size measurement system ELSZ-1000 (manufactured by Otsuka Electronics Co., Ltd.) at pH 7 and 25°C using a plate cell.

[0322] Specifically, the fibers were arranged in close contact with the groove for the plate without gaps, and a dispersion obtained by dispersing monitoring particles (polystyrene particles coated with hydroxypropylcellulose [manufactured by Otsuka Electronics Co., Ltd.]) in a 10 mM sodium chloride (NaCl) solution was injected into the groove for the plate. Electrophoresis was performed under the condition of applying a voltage of 80 V.

[0323] <Measurement of the Adhesion Strength between Reinforcement Fiber and EPDM Rubber>

[0324] For the reinforcing fibers obtained in Examples 1 to 7, Comparative Examples 1 to 4, and Reference Example 1, evaluation sheets were prepared by the following method, and the force (N / 25.4 mm) required to perform T-type peeling of the reinforcing fibers from the rubber was measured to evaluate the rubber adhesion. The results are shown in Table 3.

[0325] The evaluation results of the rubber adhesive force showed that the larger the numerical value, the greater the adhesive force between the reinforcing fiber and the rubber. The adhesive sheet was prepared as follows.

[0326] [Preparation of evaluation films]

[0327] The reinforcing fibers prepared in the examples, comparative examples and reference examples were arranged in a curtain-like manner on a masking tape so that the reinforcing fibers did not overlap each other and fixed, and then overlapped with an unvulcanized rubber composition prepared separately using EPDM rubber according to the following formulation. 2 The evaluation sheet was prepared by press-vulcanizing the film under the conditions of 30 minutes.

[0328] [Composition of EPDM unvulcanized rubber]

[0329] EPDM rubber: 100 parts by mass

[0330] Filler (carbon black): 60 parts by mass

[0331] Softener (paraffin-based process oil): 20 parts by mass

[0332] Crosslinking agent (sulfur powder): 1.5 parts by mass

[0333] Vulcanization aid (two kinds of lead powder, stearic acid): 6 parts by mass

[0334] Vulcanization accelerator (thiazole, thiazole): 1.5 parts by mass

[0335] [Table 3]

[0336]

[0337] <Examples 8 to 16 and Comparative Examples 5 to 10>

[0338] Reinforcing fibers were prepared by the same method as in Example 1 except that the fibers, the surface modification layer, the adhesive layer, and the amounts of adhesion thereof were changed as described in Table 4. In addition to the polyester fibers, nylon fibers (total fineness 1100 dtex, single yarn fineness 6.10 dtex) as polyamide fibers and vinylon fibers (total fineness 1330 dtex, single yarn fineness 6.65 dtex, "KURARON 1239" manufactured by Kuraray Co., Ltd.) as polyvinyl alcohol fibers were used as fiber types.

[0339] <Reference Example 2>

[0340] Reinforced fibers were produced in the same manner as in Reference Example 1 except that twisting was not finally performed.

[0341] <Measurement of the Adhesion Strength between Reinforcement Fiber and NR / SBR Rubber>

[0342] For the reinforcing fibers obtained in Examples 8 to 16, Comparative Examples 5 to 10, and Reference Example 2, evaluation sheets were prepared by the following method, and the force (N / 25.4 mm) required for T-peeling the reinforcing fibers from the rubber was measured, and the rubber bonding strength was evaluated. The results are shown in Table 4. The evaluation results of the rubber bonding strength show that the larger the value, the greater the bonding strength between the reinforcing fibers and the rubber. It should be noted that the bonding sheet was prepared as described below.

[0343] [Preparation of evaluation films]

[0344] The reinforcing fibers prepared in the above-mentioned examples, comparative examples and reference examples were arranged in a curtain-like manner on a masking tape so that the reinforcing fibers did not overlap each other and fixed, and then overlapped with an unvulcanized rubber composition prepared separately using NR / SBR rubber according to the following formulation. 2 The evaluation sheet was prepared by press-vulcanizing the film under the conditions of 30 minutes.

[0345] [NR / SBR unvulcanized rubber compounding composition]

[0346] NR rubber: 70 parts by mass

[0347] SBR rubber: 41.25 parts by mass

[0348] Filler (carbon black): 45 parts by mass

[0349] Vulcanizing agent (sulfur powder): 3.5 parts by mass

[0350] Vulcanization aid (lead, stearic acid): 6 parts by mass

[0351] Vulcanization accelerator (thiazole): 1 part by mass

[0352] [Table 4]

[0353]

[0354] <Example 17: Method for treating twisted cord>

[0355] A twisted fiber cord was prepared by applying an upper twist of 470 times / m and a lower twist of 470 times / m to two PET fibers (total fineness 1100 dtex, single yarn fineness 6.10 dtex) as polyester-based fibers to produce a cord.

[0356] After the above-mentioned twisted cord is immersed in the surface modifier (B-1), the liquid is squeezed out with a roller. The obtained fiber cord is dried at 140°C for 60 seconds and further heat-treated at 240°C for 60 seconds. Next, it is immersed in an emulsion composition having the modified conjugated diene rubber described in Table 5 as the main component, the liquid is squeezed out with a roller, and the emulsion is dried at 140°C for 60 seconds before winding. It should be noted that the content of the modified conjugated diene rubber in the emulsion composition is 10% by mass.

[0357] <Examples 18, 19 and Comparative Example 11>

[0358] Reinforcing fibers were prepared in the same manner as in Example 17 except that the surface modification layer, the adhesive layer, and the amounts of adhesion thereof were changed as described in Table 5.

[0359] <Reference Example 3>

[0360] Reinforcing fibers were produced in the same manner as in Reference Example 1 except that twisted PET fiber cords were used.

[0361] <Measurement of rubber adhesion>

[0362] For the reinforcing fibers obtained in Examples 17 to 19, Comparative Example 11 and Reference Example 3, evaluation samples were prepared by the following method, and the force (N / 3 strips) required for T-peeling the reinforcing fibers from the rubber was measured, and the rubber bonding strength was evaluated. The results are shown in Table 5. The evaluation results of the rubber bonding strength indicate that the larger the value, the greater the bonding strength between the reinforcing fibers and the rubber. It should be noted that the bonding samples were prepared as described below.

[0363] <Preparation of evaluation samples>

[0364] The three reinforcing fibers prepared in the above-mentioned examples, comparative examples and reference examples were arranged at a certain interval on the NR / SBR unvulcanized rubber composition prepared by the above-mentioned blending. 2 The adhesive test piece was prepared by press vulcanization for 30 minutes under the conditions of .

[0365] [Table 5]

[0366]

[0367] As is clear from the results of the examples and comparative examples, according to the present invention, surface-modified fibers and reinforcing fibers having excellent adhesion to rubber can be obtained. In particular, according to the present invention, fibers and rubber can be firmly bonded when an adhesive having resorcinol-formaldehyde resin and rubber latex as main components is used.

Claims

1. A reinforcing fiber having: Surface modified fibers, and an adhesive layer covering at least a portion of the surface of the surface-modified fiber and containing a conjugated diene rubber, The surface-modified fiber comprises a fiber and a surface-modified layer covering at least a portion of the surface of the fiber. The solid surface Zeta potential of the surface of the surface modification layer is -20.0 to 30.0 mV, The surface modification layer comprises a Oxazoline, A compound having one or more functional groups selected from the group consisting of an oxazolidinone group, a carbodiimide group, a ureido group, an amino group, and an aziridine group.

2. The reinforcing fiber according to claim 1, wherein The fiber is one or more fibers selected from the group consisting of polyester fibers, polyamide fibers, polyvinyl alcohol fibers, and regenerated cellulose fibers.

3. The reinforcing fiber according to claim 1 or 2, wherein The surface modification layer includes a compound having a nitrogen-containing functional group.

4. The reinforcing fiber according to claim 1 or 2, wherein The amount of the surface modification layer is 0.01 to 5.0 parts by mass based on 100 parts by mass of the fiber used as a raw material.

5. The reinforcing fiber according to claim 1 or 2, wherein The number average molecular weight Mn of the conjugated diene rubber exceeds 2,000 and is 120,000 or less.

6. The reinforcing fiber according to claim 1 or 2, wherein The conjugated diene rubber has at least one monomer unit derived from butadiene, isoprene, and farnesene in the molecule.

7. The reinforcing fiber according to claim 1 or 2, wherein The conjugated diene rubber is a modified conjugated diene rubber having a hydrogen-bonding functional group in a part of the conjugated diene rubber, and the hydrogen-bonding functional group is one or more selected from a hydroxyl group, an epoxy group, an aldehyde group, an acetalized form of an aldehyde group, a carboxyl group, a carboxyl salt, an esterified form of a carboxyl group, an anhydride of a carboxyl group, a silanol group, an esterified form of a silanol group, an amino group, an imidazole group, and a mercapto group.

8. The reinforcing fiber according to claim 1 or 2, wherein The number of hydrogen-bonding functional groups in the conjugated diene rubber is 1 to 80 per molecule on average.

9. The reinforcing fiber according to claim 1 or 2, wherein The conjugated diene rubber is in a liquid state having a melt viscosity of 4000 Pa·s or less measured at 38° C.

10. The reinforcing fiber according to claim 1 or 2, wherein The glass transition temperature of the conjugated diene rubber is -100 to 10°C.

11. The reinforcing fiber according to claim 1 or 2, wherein The conjugated diene rubber has a vinyl content of 80 mol % or less.

12. The reinforcing fiber according to claim 1 or 2, wherein The adhesive layer further contains oil having a vapor pressure of 10 Pa or less at 20°C.

13. The reinforcing fiber according to claim 12, wherein The oil is at least one selected from mineral oil, vegetable oil, hydrocarbon synthetic oil, ester synthetic oil, and ether synthetic oil.

14. The reinforcing fiber according to claim 12, wherein The flash point of the oil is above 70°C.

15. The reinforcing fiber according to claim 12, wherein The adhesive layer is formed by applying an adhesive component prepared by dissolving a conjugated diene rubber in oil to the surface-modified fiber.

16. The reinforcing fiber according to claim 15, wherein The content of the conjugated diene rubber in the adhesive component is 1 to 80% by mass.

17. The reinforcing fiber according to claim 15, wherein The content of the oil in the adhesive component is 20 to 99% by mass.

18. The reinforcing fiber according to claim 15, wherein The mass ratio of the conjugated diene rubber to the oil in the adhesive component is 0.1:9.9 to 8:2 in terms of conjugated diene rubber R:oil O.

19. The reinforcing fiber according to claim 15, wherein When the adhesive component is in the form of an emulsion, the content of the conjugated diene rubber in the adhesive component is 0.5 to 60% by mass.

20. The reinforcing fiber according to claim 1 or 2, wherein The adhesive layer does not contain formaldehyde or a resin containing formaldehyde as a raw material.

21. The reinforcing fiber according to claim 1 or 2, wherein The single fiber fineness of the reinforcing fiber is 0.1 to 30 dtex.

22. The reinforcing fiber according to claim 1 or 2, wherein The reinforcing fiber is multifilament.

23. The reinforcing fiber according to claim 1 or 2, wherein The rubber bonding force of the reinforcing fiber is 30-200N / 25.4mm.

24. The reinforcing fiber according to claim 1 or 2, wherein The rubber bonding force of the reinforcing fibers is 30-200 N / 3 fibers.

25. A molded product using the reinforcing fiber according to any one of claims 1 to 24.

26. The molded article according to claim 25, further comprising a rubber layer.

27. The molded article according to claim 25 or 26, wherein The shaped body is a tire, a belt or a tube.

28. The molded article according to claim 25 or 26, comprising fibers, a surface modification layer, an adhesive layer, and a rubber layer in this order, The adhesive strength between the adhesive layer and the rubber layer is 70 N or more per a width of 25.4 mm.

Citation Information

Patent Citations

  • Bonding of fibers for reinforcing rubbers

    JP1979004976A

  • Adhesive between rubber and fiber

    JP1983002370A

  • Adhesive, rubber hose equipped with reinforcing thread and method of manufacturing rubber hose

    JP2011111563A

  • Adsorbent carrier and column for extracorporeal circulation

    CN101151056A

  • Manufacturing method of water-repellent textiles

    CN107435245A